RETRACTED: Can the Kanguru Mother Care (KMC) intervention improve breast milk production? - Agustina, Ayuda Nia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Retraction NoticeFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Aisyah: Jurnal Ilmu Kesehatan to an article entitled “Can the Kanguru Mother Care (KMC) intervention improve breast milk production?” Vol 6, No 1, pp. 75-84, March 2021, DOI: http://doi.org/10.30604/jika.v6i1.431This paper has been found to be in violation of the Jurnal Aisyah: Jurnal Ilmu Kesehatan Publication principles and has been retracted (please see https://aisyah.journalpress.id/jika/about/editorialPolicies#custom-1).The article contained redundant material, the editor investigated and found that the paper published in Jurnal Keperawatan Cikini (JKC), Vol. 2, No. 1 (2021), pp. 24-34, entitled " CAN THE KANGURU MOTHER CARE (KMC) INTERVENTION IMPROVE BREAST MILK PRODUCTION?". https://www.jurnal.akperrscikini.ac.id/index.php/JKC/article/view/47The document and its content have been removed from Jurnal Aisyah: Jurnal Ilmu Kesehatan and reasonable effort should be made to remove all references to this article.